SCALES OF POLITICAL POWER ARTS, NETWORKS AND TECHNIQUES IN STUDIES ON GOVERNMENTALITY - Avellaneda, Aldo (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
This paper argues that the studies on governmentality have defined themselves by the absence of a perimeter or domain concerning to political power in order to make their analysis. They have done so for the simple reason that this is an inner phenomenon to the same arts of government. And this, far from hindering the study of complex forms of conducting conducts and the role of state, private or communal areas in them, involves the advantage of making a diagnosis from the immanence of their own modes of rendering reality. In dealing with this, I propose a close reading to these objectives of the main movements in this analytical approach. And I conclude by briefly exposing that the specific difference of governmentality studies is not so much the explicit and timely proposal on how to understand the state (it’s not one, it has no essence, etc.) but in the movement of attributing to the arts of government their own scales of political power. This is where the focus on governmental arts distances itself from many of the projects prevailing in political theory and philosophy at the beginning of the century, still competing in the high peaks of definitions.